Sperm form and function: what do we know about the role of sexual selection?. Issue 5 (May 2018) - Lüpold, Stefan; Pitnick, Scott
Abstract : Sperm morphological variation has attracted considerable interest and generated a wealth of predominantly descriptive studies over the past three centuries. Yet, apart from biophysical studies linking sperm morphology to swimming velocity, surprisingly little is known about the adaptive significance of sperm form and the selective processes underlying its tremendous diversification throughout the animal kingdom. Here, we first discuss the challenges of examining sperm morphology in an evolutionary context and why our understanding of it is far from complete. Then, we review empirical evidence for how sexual selection theory applies to the evolution of sperm form and function, including putative secondary sexual traits borne by sperm.